İŞGALLERİNDEN ÖNCE TÜRKİSTAN HANLIKLARINDA TARİH YAZICILIĞI - Muhammed Bilal Çelik (Turkish History Education Journal, 2014)
From the beginning of 16th century, in Turkestan, political structures whose rulers were the descendants of Chinggis Qaghan and Muslim, and whose population was Turkish and Muslim had emerged. These states, called Turkestan Khanates and their rulers as khan, in supplying their legitimacy, on the one hand they stress to be the descendants of Chinggis Qaghan, on the other hand, to keep the Muslim people on their side they have given importance to the Islamic discourse. The historical records of khanates of Bukhara, Khiva, Khoqand and Kazakh which were established in the Western Turkestan and invaded by Russia from the second quarter of the 18th century, and Yarkend Khanate and Khojas State which * Doç. Dr., Sakarya Üniversitesi, Fen-Edebiyat Fakültesi, Tarih Bölümü. E-posta: bcelik@sakarya.edu.tr were established in Eastern Turkestan and invaded by China from the second half of the 18th century will be the subject of this paper. The great part of the sources is not studied and their language is largely in Persian, a minority is in Turkish. Majority of works have been focused on political issues, while less space is given to the economic and social events. Values of the society the historiographers live in were affected them. Thus, the phrases, especially in Islamic discourse, are remarkable. Analyzing works, sometimes probably due to political weakness and the absence of historiographers, the historical events were recorded by the rulers and they undertook the job itself. To the sources it was started by the creation of the world, or by the reigning dynasty up to the time of the author, or dedicated these works to the biography of a monarch. Thus, the tradition of Islamic historiography has an intense effect on them. In this article, some basic characteristics, given above, of the tradition of historiography of the Turkestan Khanates, will be focused.